Variants associated with Gaucher disease in multiple system atrophy. (28th February 2015) - Mitsui, Jun; Matsukawa, Takashi; Sasaki, Hidenao; Yabe, Ichiro; Matsushima, Masaaki; Dürr, Alexandra; Brice, Alexis; Takashima, Hiroshi; Kikuchi, Akio; Aoki, Masashi; Ishiura, Hiroyuki; Yasuda, Tsutomu; et al.
Abstract Objective Glucocerebrosidase gene (GBA) variants that cause Gaucher disease are associated with Parkinson disease (PD) and dementia with Lewy bodies (DLB). To investigate the role of GBA variants in multiple system atrophy (MSA), we analyzed GBA variants in a large case–control series. Methods We sequenced coding regions and flanking splice sites of GBA in 969 MSA patients (574 Japanese, 223 European, and 172 North American) and 1509 control subjects (900 Japanese, 315 European, and 294 North American). We focused solely on Gaucher‐disease‐causing GBA variants. Results In the Japanese series, we found nine carriers among the MSA patients (1.65%) and eight carriers among the control subjects (0.89%). In the European series, we found three carriers among the MSA patients (1.35%) and two carriers among the control subjects (0.63%). In the North American series, we found five carriers among the MSA patients (2.91%) and one carrier among the control subjects (0.34%). Subjecting each series to a Mantel–Haenszel analysis yielded a pooled odds ratio (OR) of 2.44 (95% confidence interval [CI], 1.14–5.21) and a P‐value of 0.029 without evidence of significant heterogeneity. Logistic regression analysis yielded similar results, with an adjusted OR of 2.43 (95% CI 1.15–5.37) and a P‐value of 0.022. Subtype analysis showed that Gaucher‐disease‐causing GBA variants are significantly associated with MSA cerebellar subtype (MSA‐C) patients (P = 7.3 × 10−3). Interpretation The findings indicate that, as in PD and DLB, Gaucher‐disease‐causing GBA variants are associated with MSA.